Voltage Stability Control of Boost Converter Using Linear Quadratic Integrator - Muthmainnah, Nurul Fitri; Al Tahtawi, Adnan Rafi; Baisrum, Baisrum (Peneliti Teknologi Teknik Indonesia, 2023)
This paper proposes an optimal control design to regulate output voltage of DC/DC boost converter. Linear Quadratic Integrator (LQI) was designed by determining Q and R weighting matrices in order to minimize error output voltage on several disturbance scenarios. The state-space average model of the boost converter is generated using MATLAB/Simulink, while the controller gain is obtained using LQI function on MATLAB/M-file. We also conduct simple hardware experiment using Arduino board as the main controller. The simulation results for the two test scenarios, namely changing input condition and changing load condition show an IAE value was less than 0.2. In the hardware experiment result, the steady-state error value was less than 9.5% for the both test scenarios.